Skin Diseases in Kidney Transplant Recipients - Zamanian, Abbas; Mahjub, Hossein; Mehralian, Azame (Urology Journal, 2009)
Introduction: The aim of this study was to evaluate the frequency of skin diseases in kidney transplant recipients. Materials and Methods: This cross-sectional study was performed on 233 kidney transplant recipients in Ekbatan Hospital of Hamedan in 2004. The patients were examined by a dermatologist and diagnosis was made on the basis of clinical observations. Biopsies and scraping of the lesions were taken whenever necessary. Results: Of the patients, 226 (97%) suffered from one or more skin lesions. The most common lesions were drug related, including hypertrichosis, gingival hyperplasia, acne, and cushingoid feature which were detected in 86.7% of the patients. Also, infectious and premalignant or malignant lesions (actinic keratosis, squamous cell carcinoma, and basal cell carcinoma) were seen in 48.9% and 14.2% of the patients. The mean duration of immunosuppressive therapy was significantly higher in patients with infectious skin diseases (P < .001). Conclusion: Skin lesions are a significant problem in kidney transplant recipients. A careful monitoring of these patients is recommended in order to detect these lesions in early stages and treat them.